Risk factors for active syphilis and TPHA seroconversion in a rural African population. Issue 1 (1st February 2001) - Todd, J; Munguti, K; Grosskurth, H; Mngara, J; Changalucha, J; Mayaud, P; Mosha, F; Gavyole, A; Mabey, D; Hayes, R
Abstract : Objectives: Syphilis is an important cause of morbidity in sub-Saharan Africa, and a cofactor for the sexual transmission of HIV. A better understanding of the prevalence and risk factors of syphilis in African populations would help to formulate effective interventions for its prevention and treatment. Methods: The prevalence and incidence of syphilis were obtained from a cohort recruited in Mwanza, Tanzania. Two unmatched case-control studies nested within the cohort provide information on potential risk factors. Results: The prevalence of active syphilis (TPHA positive and RPR positive any titre) was 7.5% in men and 9.1% in women, but in youths (aged 15–19 years) the prevalence was higher in women (6.6%) than in men (2.0%). The incidence of TPHA seroconversion was highest in women aged 15–19 at 3.4% per year, and around 2% per year at all ages among men. A higher prevalence of syphilis was found in those currently divorced or widowed (men: OR=1.61, women: OR=2.78), and those previously divorced or widowed (men: OR=1.51, women: OR=1.85). Among men, prevalence was associated with lack of circumcision (OR=1.89), traditional religion (OR=1.55), and reporting five or more partners during the past year (OR=1.81) while incidence was associated with no primary education (OR=2.17), farming (OR=3.85), and a self perceived high risk of STD (OR=3.56). In women, prevalence was associated with no primary education (OR=2.13), early sexual debut (OR=1.59), and a self perceived high risk of STD (OR=3.57), while incidence was associated with living away from the community (OR=2.72). Conclusion: The prevalence and incidence of syphilis remain high in this rural African population. More effort is needed to promote safer sexual behaviour, and to provide effective, accessible treatment. The high incidence of syphilis in young women calls for sexual health interventions targeted at adolescents.